A new species of Cactopinus Schwarz from central Mexico (Coleoptera: Curculionidae: Scolytinae) - Atkinson, Thomas H. (Zootaxa, 2016)
A new species in the genus Cactopinus Schwarz is described from central Mexico bringing the total of known species to 22.